Implementasi Kebijakan Disiplin Aparatur Sipil Negara Pada Sekretariat Dewan Perwakilan Daerah Kabupaten Mamuju - Muhammad Akbar S; Yenni Yenni (Universitas Muhammadiyah Makassar, 2026)
This research aims to determine the implementation of state civil servant discipline policies at the secretariat of the regional people's representative council of Mamuju district. This type of research is qualitative research and the type of research uses a descriptive approach. The population in this study were all civil servants at the Secretariat of the Mamuju Regency Regional People's Representative Council. Based on the research results, it can be concluded that